The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/cjoc.200990374
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Temperature‐responsive Porous Monoliths

Abstract: A new temperature-responsive porous monolith has been prepared by surface-initiated activators generated by electron transfer atom transfer radical polymerization (AGET ATRP) grafting poly(N-isopropylacrylamide) (PNIPAAm) within the pores of the porous polymer monolith. The grafting copolymerization was carried out by a method based on a continuous flow-through technique without special deoxygenation procedure needed in the general ATRP. The addition of ascorbic acid could counteract the oxidation effect of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Work to replace the liquid electrolyte with a solid hole-transport medium has been undertaken by several research groups. One of the first porphyrin-based solidstate DSSCs was reported by Zhang and Xiao in 2000 [154]. The device was made up in the following order: SnO 2 /TiO 2 /TCPP/CuI/Al with CuI acting as the solid hole transporter.…”
Section: Porphyrins In Dsscsmentioning
confidence: 99%
“…Work to replace the liquid electrolyte with a solid hole-transport medium has been undertaken by several research groups. One of the first porphyrin-based solidstate DSSCs was reported by Zhang and Xiao in 2000 [154]. The device was made up in the following order: SnO 2 /TiO 2 /TCPP/CuI/Al with CuI acting as the solid hole transporter.…”
Section: Porphyrins In Dsscsmentioning
confidence: 99%
“…The retention times were prolonged, and the resolution was improved with increasing temperature. Prior reports by us and by others demonstrated that the PNIPAAm grafted silica exhibited hydrophilic property at lower temperatures than LCST, while the surfaces were hydrophobic at higher temperatures . As a result, the weak interaction between peptides and hydrophilic PNIPAAm resulted in poor separation at 10°C, whereas the enhanced hydrophobic interaction became the primary separating force at 50°C.…”
Section: Resultsmentioning
confidence: 85%
“…The surface property and function of the stationary phase is modulated by external temperature to fulfill separation requirements without changing mobile phase composition. In addition to particle‐packed column, PNIPAAm was also used to prepare thermoresponsive monolithic column on which proteins , steroids , and aromatic ketones , were well resolved with a short analysis time and relatively high column efficiency. Thermally driven separation of benzoic acid and nicotinic acid using a PNIPAAm‐grafted capillary column in electrochromatography was reported previously by our group .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their insolubleness in water, most of heavy metal pollutants will bind to the sediment and suspended solids which mostly transfer to the sediment. So the distribution of heavy metals in the sediment can reflect the pollution condition of river basin [11]. In a word, it is essential and valuable to research heavy metals of sediment in the river for the river pollution analysis.…”
Section: Introductionmentioning
confidence: 99%